Some Important Grasses of the Andaman Islands - Bhattee, S. S.; Thampi, C. J. (Indian Forester, 1963)
The findings of the observations conducted at the Soil Conservation Research Station, Rangat, Andamans and Nicobar Islands on some of the major species of grasses of the Andaman Islands are presented in this article. An effort has been made to characterize the various species of local grasses as related to soils and their growth response.